The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1098/rsta.2008.0292
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the complexity of cardiovascular regulation

Abstract: The cardiovascular system plays a key role in complex living organisms since it provides supplies for maintaining vital functions and, contemporaneously, gets rid of waste materials. It is formed by highly specialized subsystems that interact with each other to accomplish tasks (e.g. the optimization of arterial and pulmonary circulation) and even compete for resources as in, for example, the maintenance of the cerebral circulation during a massive haemorrhage. Subsystems have their own local regulatory mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 15 publications
(21 reference statements)
1
60
0
5
Order By: Relevance
“…We applied the proposed framework to face the issue of the description of the cardiovascular control from spontaneous beat-to-beat fluctuations of cardiovascular variables. This problem poses the abovementioned challenges owing to the presence of multiple, contemporaneously active, regulatory mechanisms and the lack of a strict formalization of the causal relations among them [28,29]. The proposed indexes distinguished experimental conditions, identified early signs of syncope, detected nonlinear interactions and allowed sound interpretations and the formulation of hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…We applied the proposed framework to face the issue of the description of the cardiovascular control from spontaneous beat-to-beat fluctuations of cardiovascular variables. This problem poses the abovementioned challenges owing to the presence of multiple, contemporaneously active, regulatory mechanisms and the lack of a strict formalization of the causal relations among them [28,29]. The proposed indexes distinguished experimental conditions, identified early signs of syncope, detected nonlinear interactions and allowed sound interpretations and the formulation of hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, em relação ao grupo controle, os grupos AER e AER+FOR apresentaram predomínio da modulação vagal (AFun e 2UV%) e menor modulação simpática (BFnu e 0V%). De acordo com Porta et al 19 , a complexidade da regulação cardiovascular promove informações importantes sobre os mecanismos regulatórios subjacentes. Portanto, a modificação dos índices de complexidade, neste caso, pode ser resultante da grande função do órgão, um aumento de interação entre os subsistemas e aperfeiçoamento de mecanismos de regulação, o que pode sugerir uma adaptação autonômica cardíaca.…”
Section: Discussionunclassified
“…It is well proven that schizophrenia is related to panic attacks [111,112], further supporting the altered CRC in SZ might be at least partly related to panic attacks in the acute psychotic state. It was shown that changed complexity indices, resulting from depressed organ function, a loss of interaction among subsystems, an overwhelming action of a subsystem over others and an impairment of regulatory processes, is a clear hallmark of a pathological situation [113]. We believe that the found alterations in CRC might reflect arousal and permeant stress situation in acutely ill SZ patients.…”
Section: Schizophrenia: Cardiorespiratory Systemmentioning
confidence: 93%